PELATIHAN GIZI DAN KESEHATAN REMAJA MELALUI IMPLEMENTASI PROGRAM NUTRITION GOES TO SCHOOL BAGI PESANTREN KABUPATEN BOGOR - ade saputra nasution; Jesus C Fernandez; Retty Putri Utami Dwipa (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2024)
This community service activity aims to improve the knowledge and skills of teachers, canteen managers, kitchen managers, and pesantren administrators in Bogor Regency about adolescent health and nutrition. The Nutrition Goes to School program, which focuses on teaching administrators and managers about balanced nutrition and healthy lifestyles, was implemented to support this program. The implementation methods included lectures, interactive discussions, simulations of nutritious menu preparation, and BMI measurement, involving 14 participants. The results of the training showed a significant increase in participants' knowledge, with an average score increase of 22% in both the pre-test and post-test. In addition, participants were able to make a balanced nutrition implementation plan for santri and apply the knowledge learned through direct practice. The importance of the concepts of health promotion and behavior change in the educational environment shows the contribution of this activity to science in the field of education. This activity successfully combines health education with the daily practices of pesantren with a participatory approach, which results in a healthier learning environment and supports adolescent development. In addition, this program can serve as a model for implementing adaptive health education for similar environments in the future.